Interpretation of Farid Esack's Hermeneutics as a Value of Social Movement Transformation - Syahrul; Syarifaturrahmatullah; Mahbub Humaidi Aziz; Moh. Buny Andaru Bahy; Bima Fandi Asy’arie (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
The slogan apartheid by the National Party that governs black life in South Africa caused turmoil and harsh criticism both inside and outside Africa. The establishment of The Call of Islam organization in 1984, initiated by Esack with the idea of liberation derived from his hermeneutic concept, was one of the forms of resistance. This study discusses the idea of Esack's hermeneutics in-depth and presents a form of Qur'an reading with Esack's hermeneutics in strengthening social movements. This paper uses a qualitative approach with a library research model. Primary data are taken from books by Esack related to hermeneutics and social movements. At the same time, secondary data is in the form of articles and writings related to his thoughts and social movements. The results showed that Esack's hermeneutics combined Arkoun's regression-progressive model and Fazlurrahman's double movement. Esack's hermeneutics has six interrelated interpretation keys and aims to liberate the oppressed from the ruler's tyranny. The six keys in question are Taqwa, Tawhid, Al-Nas, Al-Mustadh'afun fi Al-Ardh, Al-Adl, Al-Qisth, and Jihad. Social movements inspired by Esack's hermeneutics include the Muslim Student Association (MSA), Muslim Youth Movement (MYM), Qiblah, and The Call of Islam. The forms of resistance are anti-apartheid (jihad and shahada), racism jihad (against racism), socio-economic jihad (for development, reconstruction, and against poverty), and gender jihad.